PENERAPAN SISTEM INFORMASI AKUNTANSI DALAM MENINGKATKAN KUALITAS INFORMASI AKUNTANSI PADA PUSKESMAS BATUI KABUPATEN BANGGAI: APPLICATION OF ACCOUNTING INFORMATION SYSTEM IN IMPROVING THE QUALITY OF ACCOUNTING INFORMATION AT PUSKESMAS BATUI, BANGGAI REGENCY - Yusni Yusni; Fitriani Fitriani; Arisanjaya Doloan (Yayasan Education and Social Center, 2023)
This study aims to find out how the application of accounting information systems in improving the quality of accounting information at the Batui Health Center. This research is important for providing advice to the Batui Health Center. Suggestions for accounting information systems for cash receipts at the Batui Health Center will be considered in planning a good accounting information system. The system can meet the information needs of the Community Health Center in accordance with the quality characteristics of an adequate accounting information system. The type of research data is descriptive qualitative. Sources of data used are primary data and secondary data. Data collection techniques used are3 observation, interviews and documentation. The results of this study indicate that the system applied to the puskesmas is good enough. This can be seen from the related sections starting from patient registration until patient discharge which is equipped with several documents such as medical record documents, proof of payment, and letters of deposit. As well as the separation of functions, namely operational functions, receiving functions and recording and deviation functions. Likewise with the procedures that have been carried out in accordance with the authority, but it is necessary to add employees to the cashier. The quality of accounting information seen from the characteristics of the cash receipts system, usefulness, reliability, simplicity, flexibility and capacity is sufficient